1959
DOI: 10.2105/ajph.49.12.1630
|View full text |Cite
|
Sign up to set email alerts
|

A Short-Term Community Study of the Epidemiology of Coronary Heart Disease

Abstract: This is an epidemiological study of coronary heart disease in a general population in North Dakota. A number of provocative findings appear in this preliminary report. Among them is the differential risk of developing coronary disease as between farmers and other occupational groups, and the role of factors other than diet in determining the development of the condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
1
1

Year Published

1969
1969
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(23 citation statements)
references
References 1 publication
3
18
1
1
Order By: Relevance
“…Conductors were found to have much lower risk for CVD compared with the drivers. After this study other studies conducted on letter-carriers and mail clerks 4 , farmers and sedentary townsmen 5,6 , railroad track workers and clerks 7,8 and longshoremen loading cargo into ships or tallying it into warehouses 9,10 reached similar conclusions. Today, it is well known that physical inactivity is related to an increased risk for CVD 11 and also to other disease states such as hypertension, non-insulin-dependent diabetes mellitus, osteoporosis, obesity and certain forms of cancer 12 .…”
mentioning
confidence: 56%
“…Conductors were found to have much lower risk for CVD compared with the drivers. After this study other studies conducted on letter-carriers and mail clerks 4 , farmers and sedentary townsmen 5,6 , railroad track workers and clerks 7,8 and longshoremen loading cargo into ships or tallying it into warehouses 9,10 reached similar conclusions. Today, it is well known that physical inactivity is related to an increased risk for CVD 11 and also to other disease states such as hypertension, non-insulin-dependent diabetes mellitus, osteoporosis, obesity and certain forms of cancer 12 .…”
mentioning
confidence: 56%
“…Surprisingly, case-control studies that investigated the association between SFA intake and the risk of CHD are few and only seven studies were identified. Early studies from North Dakota (Zukel et al, 1959), Ireland (Finegan et al, 1968), Japanese and Hawaiian cohorts in Hawaii (Bassett et al, 1969) and the Scottish Heart Health cohort (Bolton-Smith et al, 1992) did not find a difference in the % calorie intake of SFAs between cases and control subjects. Later studies employed multiple logistic regression analyses to measure risk.…”
Section: Case-control Studiesmentioning
confidence: 96%
“…In post-war America, epidemiologists set up many prospective studies (34)(35)(36)(37)(38)(39). The most famous and influential was -and is -the Framingham Heart Study.…”
Section: Early Heart Disease Epidemiology -Ancel Keys and The Framinghamentioning
confidence: 99%